(untitled) (Nigerian Journal of Technology, 2024)
Tar sand, an aggregate of sand, clay, water and bitumen was sampled from Okitipupa area of Ondo State, Nigeria, extracted and optimized using n-hexane and toluene in a soxhlet extractor to determine solvent effectiveness in extracting the bitumen content and their environmental effect. The experiment was carried out by heating the solvent at and above their boiling temperatures solely to get an optimum yield at a temperature and time of extraction of oil from the tar sand. The analysis gave an optimal yield of 9.07 % at 75oC in 4 h when n-hexane was used and an optimal yield of 21.27 % at 120oC in 4 h when toluene was used. A drastic change in colour was also notice in the sand residue to almost sandy soil nature when toluene was used as solvent compare to when n-hexane was used which shows a slight change from its blackish nature. The change in colour of the black tar sand is an indication of high extraction efficiency. Hence, owing to high demand for conventional oil supply in the country and the urgent need for an alternative source of oil, the bitumen extract can serve as an alternative source of unconventional oil supply in Nigeria and feedstock in refineries.